Blending process and genre approaches in teaching academic writing to first-year English as a second language students - Maluleke J, Mzamani (JEES (Journal of English Educators Society), 2024)
The article aims to provide a comparative analysis of the approaches employed by lecturers e to teach academic writing to first - year English as a second language (ESL) students at the university level. Lecturers are typically expected to adopt either the genre - based or process - oriented approach when instructing students from diverse multilingual and multicultural backgrounds, who possess varying levels of English proficiency. The process - genre approach is recommended by the researcher as it effectively enhances students’ academic writing abilities. The study utilized pre- and post-tests to evaluate the academic writingskills of first-year students. The pre-test served as an initial evaluation of the participants’ writing proficiency, providing a baseline for improvement, while the post-test measured progress after several weeks of instruction. Additionally, a questionnaire was administered to gather students’ perspectives on academic writing. The findings indicate that many ESL students face challenges of managing course content while simultaneously grappling with the grammatical, lexical, and syntactic complexities of the target language. Consequently, lecturers are encouraged to apply the process - genre approach to support students in improving their academic writing skills and bridging the gap between secondary and tertiary education. HIGHLIGHTS: ESL students experience challenges in writing coherent, logical, and grammatically correct essays. ESL struggle to manage course contents while struggling with grammatical, lexical and syntactic complexities of the target language. Blending the process and genre approaches helps students to improve their academic writing levels.